Validity of first-time diagnoses of congenital epidermolysis bullosa in the Danish National Patient Registry and the Danish Pathology Registry - Kristensen, Mattias Hedegaard (Clin Epidemiol, 2019)
PURPOSE: Congenital epidermolysis bullosa (CEB) is a group of rare monogenic genodermatoses. Phenotypically, the diseases vary in both severity and dissemination, which complicates studies of their epidemiology. To investigate the potential of using the Danish National Patient Registry (DNPR) for epidemiological research on CEB, we examined the positive predictive value (PPV) of a first-time diagnosis of CEB. METHODS: We identified patients with a record of CEB in DNPR and the Danish Pathology Registry (DPR) during January 1, 1977, until December 31, 2015. We restricted diagnoses from two dermatological departments and one regional hospital. Diagnoses in the DNPR are coded by the eighth and tenth revisions of the ICD (ICD-8 and ICD-10) and in the DPR by the Systematized Nomenclature of Medicine (SNOMED). We used clinical description in medical records, family history, histological findings, and molecular genetic investigations to validate diagnoses and classified them as rejected and confirmed. We estimated PPVs for any diagnosis, according to coding systems used, and for additional subdivisions of ICD-10 codes. RESULTS: We identified 116 cases from the hospital departments investigated and evaluated 96 medical records for validity. The overall PPV for probable CEB was 62.5% (95% CI: 52.5–71.5). For ICD-8, ICD-10, and SNOMED codes, the PPVs were 30.8% (95% CI: 11.4–57.7), 76.7% (95% CI: 65.8–84.9), and 0.0% (95% CI: 0.0–21.7), respectively. For the ICD-10 codes, we found the highest PPVs for diagnoses arising from the dermatological departments. For subdivisions of ICD-10 codes, PPVs were high for epidermolysis bullosa simplex and dystrophica. CONCLUSION: The PPVs for first-time diagnoses of CEB registered in the two Danish nationwide registries investigated, DNPR and DPR, ranged from low to average. We therefore recommend that these data be used with caution and restricted to ICD-10 diagnoses from specialized dermatological departments.